Analisis Pendidikan Islam Pesantren Klasik Hingga Modern - Kahfi, Muhammad Ray (Maliki Interdisciplinary Journal, 2024)
Islamic education continues to develop over time, as well as the development of Islamic education institutions which are increasingly growing and adapting to the demands of the times. But in essence the methodology and basic concepts applied in classical and modern Islamic education are the same and refer to the Islamic education system in the days of Nubuwat and Salafunassholih. Where the various systems that have emerged have aspects of the same goal, eliminate ignorance and carry out worship and equip themselves for worldly and ukhrowi life. The analysis study here aims to find out the history, differences and similarities that can be found in the classical until modern Islamic education system, especially in Islamic boarding school-based educational institutions. Keywords: Education, Islam, Islamic Boarding School.